Empirical Analysis of the Relationship between Basic Energy Sources and the Tourism Sector Index - Muradzada, Imangulu; Akbulev, Nurkhodza (International Journal of Energy Economics and Policy, 2023)
In the study, the short-term causality relationship between oil and natural gas prices, which are the main energy sources, and the XTRZM index was analysed with the Granger causality test. The DCC-GARCH model was used. Analyses were carried out over the monthly closing values between 02.01.1997 and 01.12.2022. According to the Granger causality test findings, the reason for both Brent oil and Crude Oil WTI in the XTRZM index is that Brent oil is the cause of Crude Oil WTI. It has been concluded that natural gas, Brent oil, and crude oil are not the causes of the XTRZM index and each other. Because Brent oil and crude oil are not included in the WTI XTRZM index, it has been determined that there is unidirectional Granger causality from the XTRZM index to Brent oil and crude oil WTI. According to the findings obtained from the DCC-GARCH model, there is a positive correlation between natural gas, Brent oil, crude oil, and the BIST tourism index.